PROBLEMATIKA YURIDIS LEGISLASI SYARIAT ISLAM DI PROVINSI NANGROE ACEH DARUSSALAM - Fauzi, Muh (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2012)
NanggroeÂ AcehÂ DarussalamÂ (NAD)Â inÂ theÂ reformÂ eraÂ is authorizedÂ returnedÂ to implementÂ SharÄ«ah (Islamic law). Its authority is justified by the l egal basis: Law No. 44 of 1999 on Privileges of Aceh, Law No. 18 of 2001 on Special Autonomy for the Province of Aceh as Nanggroe Aceh Darussalam, and Law No. 11 of2006 regarding the Government of Aceh. From this legal basis, then followed by the formulation of regulations ( QÄnÅ«n) at theÂ provincialÂ level.Â ButÂ legislationÂ ofÂ implementi ngÂ shari'ahÂ lawÂ inÂ NADÂ contains problematic juridical. For instance: determining ofsanctions, in the form of whipping and one or two years imprisonment, considered against legislation in higher level. Another problem is that Syar'iyyah Court positions still below on the Supreme Court (MA) as the highest court. The efforts to open â€œspecial roomâ€ of Supreme Court in NAD is seen as a solution not to take it below on the Supreme Court, seen a contrary to the laws and regulationsÂ areÂ higher.Â Likewise,Â theÂ competenceÂ ofÂ Syar'iyyahÂ CourtÂ particularlyÂ in handling a criminal cases is still obscure and there is a clash with the competence of the District Court.***ProvinsiÂ NanggroeÂ AcehÂ DarussalamÂ (NAD)Â padaÂ eraÂ reformasiÂ diberiÂ kewenangan kembali untuk melaksanakan syariat Islam. Kewenangan ini dilandaskan pada payung hukum berupa UU No. 44 Tahun 1999 tentang Keistimewaan Aceh, UU No. 18 Tahun 2001 tentang Otonomi Khusus bagi Provinsi Daerah Istimewa Aceh sebagai Provinsi Nanggroe Aceh Darussalam, dan UU No. 11 Tahun 2006 tentang Pemerintahan Aceh. Payung hukum tersebut kemudian ditindaklanjuti dengan pembuatan Perda atau QÄnÅ«npada tingkat Provinsi NAD. Namun legislasi pelaksanaan syariat Islam di Provinsi NAD mengandung problematika yuridis. Penentuan bentuk sanksi berupa cambuk dan kadar sanksiÂ berupaÂ penjaraÂ 1Â (satu)Â atauÂ 2Â (dua)Â tahunÂ b ertentanganÂ denganÂ peraturan perundang-undanganÂ yangÂ lebihÂ tinggi.Â ProblemÂ lainÂ adalahÂ masihÂ bertumpunya peradilanÂ MahkamahÂ Syarâ€˜iyyahÂ padaÂ MahkamahÂ AgungÂ (MA)Â sebagaiÂ puncakÂ peradilan. Upaya pembukaan â€œkamar khususâ€ MA di Provin si NAD yang dipandang sebagai solusi agar tidak bertumpu pada MA, justru bertenta ngan dengan peraturan perundangundanganÂ yangÂ lebihÂ tinggi.Â DemikianÂ juga,Â kompetensiÂ MahkamahÂ Syarâ€˜iyyah khususnya dalam menangani perkara pidana masih kabur dan terjadi benturan dengan kompetensi Pengadilan Negeri.***Keyword: syariat Islam, Provinsi NAD, Mahkamah Syarâ€™iyyah, yuridis